La reciprocidad puesta a prueba. Hacia una fenomenología social del cambio climático en sociedades pastoriles del sur andino peruano - Flores Moreno, Adhemir (2015)
Given that the pastoral societies of the Peruvian Andes have seldom participated in scientific and political debates about climate change, this paper aims to explain and account for the languages of beliefs, meanings, and experiences of those principally affected from a philosophical and anthropological approach. In a time of ecological crisis, not only is the world of certainties or the significant experiences of the highland shepherds put into question, but also there is an opportunity forthe critique of the relationships of reciprocity in the totality of what exists, offering answers to various inquiries through different interpretative paradigms or language games. With the same strength with which the accounts of the peasants are able to show that crisis, critic, and creation go essentially hand-in-hand, there rises the need to establish limits to the scientific or dogmatic pretention of reducing the debate about climate change solely to closed decisions of expert groups or autonomous power centers, apart from all political process of discussion and dialogue with those mainly affected. Thence comes the ethical demand to initiate processes of democratization that can give a voice to the marginalized and include them in the procedures of public deliberation about climate change by means of reciprocity, social cooperation, and symbolic exchanges on equal standing.